alexaq
contestada

****Please help me with this math problem!!**** Will give stars, thanks, and brainliest!! Josh solved the equation below. Is his solution correct? Explain why or why not. (Please show work) x^2-6x-7=0 x^2-6x+7\x^2-6x+9=7+9 (x-3)^2=16 x-3=16 x=19 x-3=-16 x=-13 I am pretty sure he messed up when he decided he needed to do x-3 twice, because when there is a +/- sign is the only time you would do x-3 then x+3, right?

Respuesta :

Graphical form: x^2-6*x-7=0x^2-6*x+7x^2-6*x+9=7+9*(x-3)^2=16x-3=16x=19x-3=-16 simplifies to x^2-6*x-7=-12*x+7*x^2+9=9*(x-3)^2+7=16*x-3=16*x=19*x-3=-16 :  
simplify( x^2-6*x-7=0x^2-6*x+7x^2-6*x+9=7+9*(x-3)^2=16x-3=16x=19x-3=-16)

Hope this helps